Empowerment of the “Sinar Bahagia” Cocoa Farmers Group in Bebidas Village, Wanasaba District, East Lombok Regency Through Diversification of Cocoa Bean Processing - Semariyani, A.A. Made; Setianingsih, Ni Luh Putu Putri; Yasa, I Wayan Sweca; Saloko, Sartijo; Singapurwa, Ni Made Ayu Suardani; Suriati, Luh; Sudiarta, Wayan; Mangku, I Gede Pasek; Wibawa, Putu Rizky Ari Yasa (PT FORMOSA CENDEKIA GLOBAL, 2024)
Bebidas Village is one of the villages in Wanasaba District, East Lombok Regency, which has relatively potential to be developed into a cocoa production center. There are two main obstacles faced by farmers, namely the lack of knowledge, attitudes, and skills of cocoa farmers towards cocoa farming management and cocoa bean processing technology into various commercial products and the absence of a standard procedure to produce quality dry cocoa beans. This community service activity aims to assist in processing cocoa plant products into various cocoa products with economic value to increase the income of cocoa farmers in Bebidas Village, Wanasaba District, East Lombok Regency. This activity can increase the productivity of cocoa plants and increase the types of processed cocoa plant products with commercial value.